Effectiveness of 3 months of rifampicin and isoniazid chemoprophylaxis for the treatment of latent tuberculosis infection in children. Issue 8 (7th June 2010) - Bright-Thomas, R; Nandwani, S; Smith, J; Morris, J A; Ormerod, L P
Abstract : Background/setting: Treatment for 3 months with rifampicin (R) and isoniazid (H) (3RH) for latent tuberculosis infection (LTBI), defined as an inappropriately positive tuberculin skin test with no clinical or x-ray evidence of disease, has been used locally since 1989. The efficacy of this regimen in children in the UK has only been studied indirectly. The long-term outcome of those children treated with 3RH, in the Chest Clinic of this high tuberculosis (TB) incidence district, has been studied to derive a more direct assessment of effectiveness. Methods: All children treated with 3RH for LTBI from 1989 to 2004 inclusive were matched with the local patient administration system (PAS), GP registration and local TB notification databases. Only those persons still registered locally on PAS, or locally GP registered were then checked for subsequent TB notification. Results: A total of 334 patients were identified, of whom 252 remained locally, with 82 lost to follow-up; 3 cases of clinical TB developed in the 252 (1.19%), with 3113 years observation (mean 12.35 years) giving 0.964/1000 person years (95% CI 0.199 to 2.816). Sensitivity analyses showed a 'best case' scenario of 0.727/1000 person years (95% CI 0.15 to 2.12), and if 10% of those lost to follow-up developed clinical TB of 2.66/1000 person years (95% CI 1.33 to 4.77). Conclusions: Follow-up of those cases treated with 3RH, for a mean of 12.35 years, and over 3100 patient years observation, shows a rate of active TB of under 1/1000 patient years. This suggests that 3RH has very high efficacy when used to treat LTBI in children in the UK and compares favourably with the expected untreated TB rate.